2002
DOI: 10.1080/080352502753458021
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug events in children during hospitalization and after discharge in a Norwegian University Hospital

Abstract: ADEs, mainly gastrointestinal, CNS and skin reactions related to drugs affecting the nervous system, anti-infectives and antiasthmatics, were seen in 28% of the patients. The reporting of events by parents was a useful supplement to the screening of patient records.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 25 publications
(36 reference statements)
2
31
0
Order By: Relevance
“…The severity of events was reported in five studies12 18 20 21 23: in two no severe ADRs were reported,20 23 while in the other three the percentage of severe ADRs ranged between 2% and 30%. Six studies reported the criteria for causality assessment,12 18 19 20 21 23 five of which used the WHO criteria 12 18 19 20 21.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The severity of events was reported in five studies12 18 20 21 23: in two no severe ADRs were reported,20 23 while in the other three the percentage of severe ADRs ranged between 2% and 30%. Six studies reported the criteria for causality assessment,12 18 19 20 21 23 five of which used the WHO criteria 12 18 19 20 21.…”
Section: Resultsmentioning
confidence: 96%
“…One additional study was identified after the manual search 12. Three studies performed in the United States were subsequently excluded because their data involved ADEs and not ADRs and one because adults were also involved 13 14 15 16…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations